THE EFFECT OF SERVICE QUALITY AND WORK DISCIPLINE ON COMMUNITY SATISFACTION AT THE CIJEDIL DISTRICT OFFICE, CIANJUR - Tuti Herawati (BAIK Publishers, 2026)
This study aims to analyze the effect of service quality (X1) and work discipline (X2) on community satisfaction (Y) at the Cijedil District Office in Cianjur. This research employs a quantitative explanatory approach. Data were collected through structured questionnaires distributed to 100 respondents who had received public services at the district office. The data were analyzed using simple and multiple linear regression with SPSS. The results show that service quality has a positive and significant effect on community satisfaction, with a correlation coefficient of 0.686 and a coefficient of determination of 47.1%. Work discipline also has a positive and significant effect on community satisfaction, indicated by a correlation coefficient of 0.743 and a determination coefficient of 55.2%. Furthermore, service quality and work discipline simultaneously have a strong and significant effect on community satisfaction, with a multiple correlation coefficient of 0.794 and an R Square value of 0.630. This indicates that both variables jointly explain 63.0% of the variation in community satisfaction, while the remaining 37.0% is influenced by other factors not examined in this study. Hypothesis testing confirms that service quality and work discipline individually and simultaneously have statistically significant effects on community satisfaction. These findings demonstrate that improving service standards and strengthening employee discipline are essential strategies for enhancing public satisfaction. This study concludes that community satisfaction is strongly influenced by both technical service quality and employee work discipline. Therefore, local government institutions are encouraged to continuously improve service procedures and reinforce disciplinary practices to achieve higher levels of public satisfaction and better service performance.